Chemical composition and antioxidant properties of extracts of fresh fruiting bodies of pleurotus sajor-caju (Fr.) singer - Kanagasabapathy, G.; Malek, S.N.A.; Kuppusamy, U.R.; Vikineswary, S. (2011)
The chemical composition and in vitro antioxidant activity of aqueous butanol and ethyl acetate extracts of Pleurotus sajor-caju were investigated in this study. Twenty-two compounds comprising methyl esters, hydrocarbon fatty acids, ethyl esters, and sterols were identified in ethyl acetate extracts, while cinnamic acid, nicotinamide, benzeneacetamide, and 4-hydroxybenzaldyhde were identified in butanol extracts by gas chromatography-mass spectrometry and NMR analysis. The antioxidant activity was determined by a beta-carotene bleaching method, ferric reducing antioxidant power, trolox equivalent antioxidant capacity, and lipid peroxidation assays, while the total phenolic content in P. sajor-caju was assessed by Folin-Ciocalteau's method. The aqueous and butanol extracts exhibited the highest antioxidant activity, corresponding to the total phenolic content. The subfractions from the ethyl acetate extract (EP1, EP2, EP3, and EP4), however, showed moderate antioxidant activity. The regular consumption of P. sajor-caju as a part of our diet may render nutritional and nutraceuticals benefits for good health.